A Clustering Algorithm for Evolving Data Streams Using Temporal Spatial Hyper Cube - Al?amri R.; Murugesan R.K.; Almutairi M.; Munir K.; Alkawsi G.; Baashar Y. (MDPI, 2023)
As applications generate massive amounts of data streams, the requirement for ways to analyze and cluster this data has become a critical field of research for knowledge discovery. Data stream clusterings primary objective and goal are to acquire insights into incoming data. Recogniz-ing all possible patterns in data streams that enter at variable rates and structures and evolve over time is critical for acquiring insights. Analyzing the data stream has been one of the vital research areas due to the inevitable evolving aspect of the data stream and its vast application domains. Existing algorithms for handling data stream clustering consider adding various data summarization structures starting from grid projection and ending with buffers of Core?Micro and Macro clusters. However, it is found that the static assumption of the data summarization impacts the quality of clustering. To fill this gap, an online clustering algorithm for handling evolving data streams using a tempo?spatial hyper cube called BOCEDS TSHC has been developed in this research. The role of the tempo?spatial hyper cube (TSHC) is to add more dimensions to the data summarization for more degree of freedom. TSHC when added to Buffer?based Online Clustering for Evolving Data Stream (BOCEDS) results in a superior evolving data stream clustering algorithm. Evaluation based on both the real world and synthetic datasets has proven the superiority of the developed BOCEDS TSHC clustering algorithm over the baseline algorithms with respect to most of the clustering met-rics. 2022 by the authors. Licensee MDPI, Basel, Switzerland.